2016
DOI: 10.1080/23328940.2016.1148526
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in personal protective equipment in a hot, humid environment does not affect risk propensity

Abstract: We tested the hypothesis that heat stress created by light exertion in encapsulating personal protective equipment (PPE) in a hot, humid environment increases risk propensity. Ten healthy subjects (29 ± 7 y) completed 2 trials presented in a counter-balanced manner. Subjects donned encapsulating PPE, and in one trial they wore a tube-lined shirt underneath that was perfused with 5°C water. Subjects completed 2 15 min bouts of walking exercise on a treadmill at ˜50% maximal heart rate in a 32°C, 81% RH environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…For example, voluntary reductions in exercise work rate in the heat attenuate the rise in core temperature, which occur secondary to reductions in metabolic heat production (26,44,53). In addition, we (46) and others (12) have identified that mandatory and constant upper body cooling during exercise in the heat attenuates the rise in core temperature. Thus, a secondary hypothesis was that thermal behavior resulting in large reductions in skin temperature would attenuate the rise in core temperature by augmenting heat loss from the skin to the water perfused suit top.…”
Section: Discussionmentioning
confidence: 91%
“…For example, voluntary reductions in exercise work rate in the heat attenuate the rise in core temperature, which occur secondary to reductions in metabolic heat production (26,44,53). In addition, we (46) and others (12) have identified that mandatory and constant upper body cooling during exercise in the heat attenuates the rise in core temperature. Thus, a secondary hypothesis was that thermal behavior resulting in large reductions in skin temperature would attenuate the rise in core temperature by augmenting heat loss from the skin to the water perfused suit top.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the 38.9°C T re at the end of 60 minutes for E3 in this study shows the development of heat stress that could be exacerbated when HCWs need to have several 1-hour shifts within a day. Even though a recent study 14 showed that changes in neurocognitive performance during or immediately after 50 minutes of exercise in the heat wearing PPE are not noted, and another study 15 showed that risk-taking behavior is not affected by mild heat stress, it has been demonstrated that reaching T re of 39°C over 1 hour is associated with decrements in simple mental performance 16 . This is very important information for HCWs in West Africa to determine work-rest cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the objects were barbells weighing 4.1 kg, 5.4 kg, and 6.8 kg, and the two 170 remaining objects were rolled fire hoses each weighing 21.1 kg. The dexterity task has 171 previously been used in our laboratory (52). In the present study, participants were 172 instructed to secure and disassemble as many nuts and bolts as possible in 5 min.…”
Section: Experimental Protocolmentioning
confidence: 99%